2013
DOI: 10.5933/jkapd.2013.40.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Sedation Using a Nasal Cannula in Pediatric Patients

Abstract: A total of 14 children who visited the department of Pediatric dentistry of Dankook University Dental Hospital from January, 2012 to May, 2012 and decided to get dental treatment under inhalation sevoflurane deep sedation, were studied to determine the effectiveness of end-tidal sevoflurane, respiratory and cardiovascular function to analyze monitoring sheets.The Heart rate (H.R) data were mean 101.4 rate/min (76.4-135.4 rate/min). The systolic blood pressure data mean were 96.9 mmHg (84.2-109.2 mmHg) and dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(3 reference statements)
0
1
0
2
Order By: Relevance
“…Kim et al [ 6 7 ] reported cases of sevoflurane inhaled deep sedation using nasal hood and nasal cannula. Ji et al, [ 8 ] reported 14 cases dental treatment under sevoflurane sedation, but of 14 cases, only 3 were emergency dental treatment. This report analyzed dental and anesthetic records of 11 patients who had emergency dental treatment under sevoflurane sedation, by far the largest study.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 6 7 ] reported cases of sevoflurane inhaled deep sedation using nasal hood and nasal cannula. Ji et al, [ 8 ] reported 14 cases dental treatment under sevoflurane sedation, but of 14 cases, only 3 were emergency dental treatment. This report analyzed dental and anesthetic records of 11 patients who had emergency dental treatment under sevoflurane sedation, by far the largest study.…”
Section: Discussionmentioning
confidence: 99%
“…또한 세보플루란진정은 깊이 조절이 용이하며, 심혈관계 안전성이 높아 소아와 장애환자에서 적용하기 유리하다 2) . 특히 소아와 장 애인의 진정에 있어, 접근성의 향상과 적용의 효율성 때문에 선 호되며 이는 기도자극이 적고 유도와 회복이 빠르고 진정에 따 른 부작용이 적기 때문이다 3) . 세보플루란진정은 통상적으로 심 한 불안이나 불수의적인 움직임으로 행동조절이 어려운 소아와 장애인의 치과치료를 위해 깊은 진정으로 사용하고 있으며 3) , 최 근에는 치과환자들을 위한 응급 진정법으로 세보플루란진정을 시행하고 있다 4,5) .…”
unclassified
“…특히 소아와 장 애인의 진정에 있어, 접근성의 향상과 적용의 효율성 때문에 선 호되며 이는 기도자극이 적고 유도와 회복이 빠르고 진정에 따 른 부작용이 적기 때문이다 3) . 세보플루란진정은 통상적으로 심 한 불안이나 불수의적인 움직임으로 행동조절이 어려운 소아와 장애인의 치과치료를 위해 깊은 진정으로 사용하고 있으며 3) , 최 근에는 치과환자들을 위한 응급 진정법으로 세보플루란진정을 시행하고 있다 4,5) . 그러므로 세보플루란진정은 다른 경구 흡입 진정의 실패나 외상으로 인한 치과 응급치료, 종종 발생하는 응 급질환 등에 대한 전신마취의 좋은 대안이 될 수 있다 6) .…”
unclassified